Comparison of doublet and triplet therapies for metastatic hormone-sensitive prostate cancer: A systematic review and network meta-analysis - Wang, Lei; Li, Chunxing; Zhao, Zichen; Li, Xiaojian; Tang, Chong; Guan, Zhenpeng; Sun, Feng; Gu, Jin; Li, Ningchen (Frontiers in Oncology, 2023)
BACKGROUND: The best choice of first-line treatment for metastatic hormone-sensitive prostate cancer (mHSPC) is unclear. We aimed to compare the effectiveness and safety determined in randomized clinical trials of doublet and triplet treatments for mHSPC. METHODS: Medline, Embase, Cochrane Central and ClinicalTrials.gov were searched from inception through July 01, 2022. Eligible studies were phase III randomized clinical trials evaluating androgen deprivation treatment (ADT) alone, doublet therapies [ADT combined with docetaxel (DOC), novel hormonal agents (NHAs), or radiotherapy (RT)], or triplet therapies (NHA+DOC+ADT) as first-line treatments for mHSPC. Outcomes of interest included overall survival (OS), progression-free survival (PFS) and grades 3-5 adverse events (AEs). Subgroup analyses were performed based on tumor burden. The effects of competing treatments were assessed by Bayesian network meta-analysis using R software. RESULTS: Ten trials with 12,298 patients comparing nine treatments were included. Darolutamide (DARO) +DOC+ADT ranked best in terms of OS benefits (OR 0·52 [95% CI 0·39–0·70]), but its advantages were all statistically insignificant compared with other therapy options except for DOC+ADT (OR 0·68 [95% CI 0·53–0·88]) and RT+ADT (OR 0·57 [95% CI 0·40–0·80]). In terms of PFS, enzalutamide(ENZA)+DOC+ADT (OR 0·32 [95% CI 0·24–0·44]) and abiraterone and prednisone (AAP) +DOC+ADT (OR 0·33 [95% CI 0·25–0·45]) ranked best. For patients with high volume disease (HVD), low volume disease (LVD), and visceral metastases, the optimal therapies were AAP+DOC+ADT (OR 0·52 [95% CI 0·33–0·83]), apalutamide+ADT (OR 0·52 [95% CI 0·26–1·05]) and DARO+DOC+ADT (OR 0·42 [95% CI 0·13–1·34]), respectively. For safety, AAP+DOC+ADT (OR 3·56 [95% CI 1·51–8·43]) ranked worst with the highest risk of grade 3−5 AEs. CONCLUSIONS: Triple therapies may further improve OS and PFS but may be associated with a decrease in safety. Triplet therapies could be suggested for HVD patients, while doublet combinations should still be preferred for LVD patients.